Peran Fintech dalam Mendorong Pembayaran Cashless pada Sektor Ekonomi Syariah: The Role of Fintech in Encouraging Cashless Payments in the Islamic Economic Sector - Tafana Dewi Kushandarini; Salsabil Fadiyah; Cynthia Indah Permatasari; Reinand Afwan Jani; Ludvi Nuraini; Ilham Ridho Ardhana; Dyandra Pramitha Kundera; Ahmad Nurrohim (TIJARAH: Jurnal Ekonomi, Manajemen, dan Bisnis Syariah, 2024)
Amid the rapid pace of the digital revolution, financial technology (Fintech) has emerged as a strategic factor that transforms the fundamental ecosystem of Islamic finance. This research discusses the crucial role of fintech in driving the transformation of the Islamic finance sector and its impact on enhancing financial inclusion, operational efficiency, and adherence to Islamic financial principles. This study uses a literature analysis approach to explore in detail the Islamic Fintech ecosystem. The findings indicate that fintech has significant potential in expanding access to Islamic finance for communities that were previously underserved. However, challenges such as complex regulations and limited consumer resources remain obstacles. Nevertheless, Islamic fintech services have successfully provided easier and more affordable access for individuals and small businesses to utilize Sharia-compliant financial products and services. One of the key innovations is the cashless system, which has been growing rapidly over time, contributing significantly to the advancement of the Islamic economy sector.